The Influence Of Viral Marketing, Price, And Free Shipping Promotions On Purchase Decisions For Glad2glow Skincare Products On Tiktokshop - Patrisia, Eka Salsa; Handayani, Sri; Wijaya, Ermy (Innovative Business Management Journal, 2025)
The development of digital technology and social media, such as TikTok Shop, has changed people's shopping behavior, especially among Generation Z, who prefer visual content and fast transactions. One local brand capitalizing on this trend is Glad2Glow, which uses viral marketing strategies, price, and free shipping promotions to attract consumers.This study aims to determine the influence of viral marketing (X₁), price (X₂), and free shipping promotions (X₃) on purchasing decisions (Y) for Glad2Glow skincare products on TikTok Shop. The method used was quantitative with a causal associative approach. The study sample consisted of 100 Generation Z respondents in Bengkulu city. The results of the study showed a multiple linear regression equation of Y = 3.016 + 0.341X₁ + 0.446X₂ + 0.152X₃ + 2.627. Partially, all three variables had a positive and significant effect on purchasing decisions, with price being the most dominant factor (t-test 5.576 > t-table 1.660). Simultaneously, F-test = 84.422 > F-table = 2.70, with a significance level of 0.000 < 0.05.